2003
DOI: 10.1002/gps.852
|View full text |Cite
|
Sign up to set email alerts
|

Bright light treatment improves sleep in institutionalised elderly—an open trial

Abstract: The findings add further evidence of the effectiveness of morning bright light exposure in the treatment of disturbed sleep among demented nursing home patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
5
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 23 publications
3
81
5
7
Order By: Relevance
“…Bright white light exposure in the morning improved sleep in institutionalized older adults. Fetveit and colleagues [35] demonstrated that exposure to 2 hours of bright light in the morning for at least 2 weeks substantially improved sleep efficiency of older adults living in nursing homes. Alessi et al [36] showed that five consecutive days of 30-minute exposure to sunlight, increased physical activity, structured bedtime, and control of light and noise at night resulted in a significant decrease in daytime sleeping in intervention participants compared to controls.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Bright white light exposure in the morning improved sleep in institutionalized older adults. Fetveit and colleagues [35] demonstrated that exposure to 2 hours of bright light in the morning for at least 2 weeks substantially improved sleep efficiency of older adults living in nursing homes. Alessi et al [36] showed that five consecutive days of 30-minute exposure to sunlight, increased physical activity, structured bedtime, and control of light and noise at night resulted in a significant decrease in daytime sleeping in intervention participants compared to controls.…”
Section: Previous Studiesmentioning
confidence: 99%
“…He suggested that the utility of bright light treatment for improving circadian rhythms was a synchronizing factor and that the effects declined with more severe dementia perhaps due to more severe damage to the suprachiasmic nucleus and resultant decreased sensitivity to light. Fetveit et al (2003) administered 2 hours of morning bright light (6000-8000 lux, 8-11 am for 2 weeks) and reported improved nighttime sleep efficiency, decreased nighttime wake time and sleep onset latency. Rest-activity levels also showed decreased nighttime activity and decreased mesor with no change in acrophase.…”
Section: Background/literature Reviewmentioning
confidence: 99%
“…Fetveit et al [61] demonstrated that exposure to 2 h of bright light (6000-8000 lux at the cornea) in the morning for at least 2 weeks substantially improved the sleep efficiency of 11 older adults with dementia. Alessi et al [67] showed that five consecutive days of 30-min exposure to sunlight, increased physical activity, structured bedtime and control of light and noise at night resulted in a significant decrease in daytime sleeping in intervention participants compared with controls.…”
Section: Review Figueiromentioning
confidence: 99%